Joshua S. Duclos, Wilderness, Morality, and Value - O'Brien, Kevin J. (Journal for the study of religion, nature and culture, 2023)
Joshua S. Duclos, Wilderness, Morality, and Value (New York: Lexington Books, 2022), 141 pp. $95.00 (cloth), ISBN: 9781666901368.